Stress-induced protein S-glutathionylation and S-trypanothionylation in African trypanosomes: a quantitative redox proteome and thiol analysis - Ulrich, Kathrin; Finkenzeller, Caroline; Merker, Sabine; Ruppert, Thomas; Krauth-Siegel, Renate (Antioxidants & redox signaling, 2017)
Aims: Trypanosomatids have a unique trypanothione-based thiol redox metabolism. The parasite-specific dithiol is synthesized from glutathione and spermidine, with glutathionylspermidine as intermediate catalyzed by trypanothione synthetase. In this study, we address the oxidative stress response of African trypanosomes with special focus on putative protein S-thiolation. Results: Challenging bloodstream Trypanosoma brucei with diamide, H2O2 or hypochlorite results in distinct levels of reversible overall protein S-thiolation. Quantitative proteome analyses reveal 84 proteins oxidized in diamide-stressed parasites. Fourteen of them, including several essential thiol redox proteins and chaperones, are also enriched when glutathione/glutaredoxin serves as a reducing system indicating S-thiolation. In parasites exposed to H2O2, other sets of proteins are modified. Only three proteins are S-thiolated under all stress conditions studied in accordance with a highly specific response. H2O2 causes primarily the formation of free disulfides. In contrast, in diamide-treated cells, glutathione, glutathionylspermidine, and trypanothione are almost completely protein bound. Remarkably, the total level of trypanothione is decreased, whereas those of glutathione and glutathionylspermidine are increased, indicating partial hydrolysis of protein-bound trypanothione. Depletion of trypanothione synthetase exclusively induces protein S-glutathionylation. Total mass analyses of a recombinant peroxidase treated with T(SH)2 and either diamide or hydrogen peroxide verify protein S-trypanothionylation as stable modification. Innovation: Our data reveal for the first time that trypanosomes employ protein S-thiolation when exposed to exogenous and endogenous oxidative stresses and trypanothione, despite its dithiol character, forms protein-mixed disulfides. Conclusion: The stress-specific responses shown here emphasize protein S-trypanothionylation and S-glutathionylation as reversible protection mechanism in these parasites.